INSURGENCY AND COUNTER INSURGENCY SOME CONCEPTS AND PROBLEMS - Nils Marius Rekkedal (Fakultas Hukum Universitas Trisakti, 2007)
This article is the second of three articles which present and discuss several of the key concepts in use when attempting, in a research or military context (e.g., in doctrines and regulations), to describe the different forms of insurgency. One of the assumptions in this work has been that all insurgent wars are different, with their own local or regional conditions. The author has also said that it should nevertheless be possible to try to find certain basic characteristics in these forms of warfare. We can also find in this article some of the key concepts and problems regarding insurgency, guerrilla warfare and methods of insurgency as well.